(untitled) (Journal of Hama University, 2024)
Government activity strongly affects the economy. When the government promotes any industry such as insurance, medicine, or technology, this will strengthen this sector and thus enhance its economy and support the country’s economy in general. Or through spending policy" as an economic term that means a set of measures and procedures taken by governments to influence public revenues and expenditures by changing their size or composition, in pursuit of achieving a set of goals determined by the general directions of government policy on the one hand, and the economic circumstance on the other hand.This study dealt with government factors and their impact on the growth of business volume and expansion of activities for insurance companies, where the insurance sector is considered one of the important and vital sectors, through the main role played by insurance companies in the economic system in general, in reducing risks and compensating those affected, which leads to development and stability Economic activity, through a questionnaire distributed to a number of workers in insurance companies, which included questions about the extent to which insurance companies comply with regulations and laws related to the insurance sector, It included questions about the extent to which insurance companies adhere to regulations and laws related to the insurance sector, the extent to which laws related to the insurance sector need to be updated, and their view of the impact of insurance legislation on the size of premiums for insurance companies, and the extent to which insurance laws are appropriate to the actual needs of this sector, and about tax exemptions that encourage the expansion of the activities of insurance companies. The questionnaire was analyzed using the SPSS program and appropriate statistical tests were used, such as One sample t.test. Through this study, we found that there is a statistically significant effect of governmental factors in the growth of business and expansion of the activities of insurance companies, and in increasing and diversifying their investments and partners, and the amounts they keep to meet the payment of obligations and reserves and their acceptance of insurance contracts that require reinsurance operations